Cross-Cultural Differences in Psychological Health, Perceived Stress, and Coping Strategies of University Students During the COVID-19 Pandemic - Noor Hassline Mohamed; Amoneeta Beckstein; Paul Hutchings; Pang, Nicholas Tze Ping; Shariffah Sheik Dawood; Risydah Fadilah; Katie E Sullivan; Azizi Yahaya; Jay Errol Villadolid Baral (Semmelweis University, Institute of Mental Health, Budapest, 2022)
Introduction: COVID-19 has affected the entire world, including university students. Students are likely to experience COVID-19 related stress that might adversely affect their psychological health and result in various coping strategies. Aims: This study’s objectives were to examine cross-cultural differences and the relationships between stress, psychological health, and coping among university students during the pandemic. Furthermore, the study explored whether coping strategies mediated the relationship between psychological health and perceived distress for this population. Methods: University students (n = 703) were recruited via convenience sampling from Indonesia, Malaysia, the Philippines, Thailand, the United States, and the United Kingdom. Participants completed an online quantitative questionnaire consisting of demographics, the Perceived Stress Scale, the General Health Questionnaire, and the Brief-COPE. Results: Perceived psychological distress was significantly associated with poorer general psychological health and both were associated with dysfunctional coping. For all countries, psychological health mediated the relationship between perceived distress and dysfunctional coping. Students from individualistic cultures reported higher stress and poorer psychological health when compared to those from collectivistic countries. The latter tended to engage in more emotion-focused and problem-focused coping and used more dysfunctional coping strategies than the former. Conclusions: Future research should explore other mediators and moderators that affect university students’ responses to pandemics and should include longitudinal studies with larger samples. Findings emphasize the need for providing university students with mental health support during and after COVID-19. It is important to develop and research empirically based strategies for reducing their stress and psychological distress through effective and culturally appropriate coping strategies.